2007
DOI: 10.1185/030079907x253906
|View full text |Cite
|
Sign up to set email alerts
|

ApoB/A1 and LDL-C/HDL-C and the prediction of cardiovascular risk in statin-treated patients

Abstract: In statin-treated patients with known CHD, apoB/A1 is positively associated with clinical events, whereas the LDL-C/HDL-C is not, but apoB/A1 does not increase the area under the curve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 27 publications
2
19
1
Order By: Relevance
“…ApoA1 might be a more accurate anti-atherogenic marker than HDL cholesterol. A previous report showed that the ApoB/A1 ratio is positively associated with clinical events in statin-treated patients with CAD 16) . Similar to the previous data, the ApoB/A1 ratio in the present study was positively correlated with the d-ROMs and negatively correlated son to the LDL cholesterol level, LDL/HDL cholesterol ratio and the HDL cholesterol, non-HDL cholesterol, Lp(a) and RLP cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
“…ApoA1 might be a more accurate anti-atherogenic marker than HDL cholesterol. A previous report showed that the ApoB/A1 ratio is positively associated with clinical events in statin-treated patients with CAD 16) . Similar to the previous data, the ApoB/A1 ratio in the present study was positively correlated with the d-ROMs and negatively correlated son to the LDL cholesterol level, LDL/HDL cholesterol ratio and the HDL cholesterol, non-HDL cholesterol, Lp(a) and RLP cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
“…Select epidemiologic and clinical studies have suggested that either Apo A-1 levels or the Apo B:A-1 ratio would be superior to traditional cholesterol values or ratios (eg, total cholesterol:HDL cholesterol) in predicting cardiovascular events. 8,11,24,25,30,31,35,45,48,[104][105][106]111,112 However, at this time, the potential benefits of introducing Apo A-1 to routine lipid/lipoprotein panels do not seem to outweigh their incremental costs. In the Emerging Risk Factors Collaboration, the largest pooled epidemiologic study to date, no advantage in risk prediction was found for Apo A-1 over HDL cholesterol.…”
Section: Current Guidelines and Expert Panel Recommendationsmentioning
confidence: 99%
“…15,98 Still, many clinicians justifiably contemplate which other atherogenic parameter needs to be altered to minimize atherosclerotic progression and cardiovascular events (Table 4). 8,23,24,[26][27][28][29][30][31]35,44,47,51,54,[99][100][101][102][103][104][105][106][107][108] Levels of Apo B or non-HDL cholesterol are in general superior to levels of LDL cholesterol in stratifying patient populations according to baseline (pretreatment) cardiovascular risk. With their ease of computation, their improvement in risk prediction over LDL cholesterol levels, their consistency with the current "cholesterol" paradigm familiar to practitioners, and their cost-effectiveness, non-HDL cholesterol levels seem to represent an attractive route to more informed decision making.…”
Section: Current Guidelines and Expert Panel Recommendationsmentioning
confidence: 99%
“…Different atherogenic indexes such as TC/HDLc, LDLc/HDLc, apoB/apoA-I, LDLc/apoB and non-HDLc/HDLc have been defined in an attempt to optimize the predictive capacity of the lipid profile [9], the efficiency of which has been demonstrated [10][11][12]. Although these indexes can provide information on risk factors difficult to quantify by routine analysis, and could better mirror the metabolic and clinical interactions among lipid fractions, they are under-used in cardiovascular disease prevention.…”
Section: Introductionmentioning
confidence: 99%